The Role of Digital Twin Technology in Enhancing Infrastructure Project Management and Operational Efficiency - Basith, Imtiyaz Abdul (Digital Repository of Theses - SSBM Geneva, 2025)
This thesis aimed to explore the role of Digital Twin Technology (DTT) in improving infrastructure project management and operational efficiency. It investigated how DTT enhance decision-making, minimizes costs, and mitigates challenges. The thesis also evaluated problems in integration and their effect on functional effectiveness. Furthermore, it examined the contribution of DTT to sustainability and urban infrastructure growth, specifically contextualizing smart city development projects. This thesis employed an exploratory research design using a mixed-method approach to investigate DTT’s influence and collected primary quantitative (survey), qualitative (Interviews), and secondary data. The outcomes confirmed DTT’s benefits in enhancing analytical decision-making, predictive management, and resource allocation while also outlying problems like higher application costs, skill limitations, and cybersecurity issues. Despite dissimilarities in perspectives among survey participants and interviewees, the results focused on the requirement for strategic investment, policy shift, and training initiatives to ensure efficient adoption and long-term advantages of DTT in the construction industry. This study analysed that Digital twin technology offers a ground-breaking opportunity to enhance operational effectiveness and project management for infrastructure building. By using simulations, real-time data, and predictive analytics, organizations may improve decision-making, optimize resource handling, and increase the sustainability of aging infrastructure. Before this technology can be extensively used, a number of challenges need to be addressed, including high costs, issues with system integration, the need for skilled personnel, and the culture of the organization. As the industry grows, it will be crucial to get over these challenges in order to fully exploit the potential advantages of Digital Twin technology in enhancing infrastructure development and ensuring long-term operating efficiency.